Advancements in Antibiotic Therapy: The Role and Future Scope of Ceftobiprole as a Fifth-generation Cephalosporin - Hariharan M; Sankari A; Rajanandh, MG (Pharmaceutical Science: New Insights and Developments Vol. 2, 2025)
The emergence of antibiotic resistance is a critical issue in modern medicine, significantly challenging the effectiveness of current antimicrobial agents. Among these, cephalosporins have played a central role in treating various bacterial infections. However, the rapid evolution of resistant pathogens, including those with extended-spectrum beta-lactamase (ESBL) and carbapenem-resistant mechanisms, necessitates the development of new-generation antibiotics. This chapter focuses on Ceftobiprole, a fifth-generation cephalosporin with potent activity against multidrug-resistant bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and penicillin-resistant Streptococcus pneumoniae. Ceftobiprole’s pharmacokinetics and pharmacodynamics underscore its efficacy and safety, demonstrating high tissue penetration and a stable profile in renal excretion, which supports its use in severe infections like complicated skin and soft tissue infections (cSSTIs) and community-acquired pneumonia (CAP). Its mechanism of action involves binding to penicillin-binding proteins (PBPs), especially PBP2a in MRSA, disrupting cell wall synthesis and effectively neutralizing resistant pathogens. Regulatory approvals across Europe, Canada, and additional regions highlight Ceftobiprole's success as a critical therapeutic agent, and ongoing research aims to expand its indications to hospital-acquired infections. As antibiotic resistance continues to rise, the development of advanced agents like Ceftobiprole is essential. This chapter reviews its clinical applications, history, and evolution, alongside its potential for integration into antimicrobial stewardship programs to mitigate resistance. Ceftobiprole’s broad spectrum and promising efficacy position it as a vital tool for addressing resistant infections, underscoring the importance of continued innovation in antibiotic development.